Fatores relacionados à capacidade física de membros superiores e inferiores de idosos de uma comunidade quilombola - Furtado, Brenda Natally Soares (2020)
Introduction: Ageing population is a worldwide experience, which has been happening in a speeded way in Brazil. As well as the elderly population, the number of people who define themselves as black is increasing. The black population, especially quilombola populations are known for their social and healthy vulnerability. It is known environmental, physical, socioeconomical, lifestyle and genetic factors may affect the elderly’s body functionality. That way, identifying the limits of functionality through tests of physical capacity and the factors related become relevant to early identify the functional decline. Objective: To assess the factors related to the physical capacity of upper limbs and lower limbs in quilombolas elderly people. Methodology: Cross-sectional, analytic study, with primary data collection. The research was conducted with elderly people residents in the Quilombola community of Caiana dos Crioulos, in the municipality of Alagoa Grande/PB, Brazil. The dependent variables of this study were: physical capacity of upper and lower limbs. The independent variables are: age, social economical level, per capita family income, years of study, number of residents per home, symptoms indicating depression, number of referred morbidities, number of falls, nutritional status, metabolic risk, practice of physical activity and sedentary behavior. Data were submitted to double entry, whose validation was verified through the “validate” tool and through statistics program Epi Info 7.2 Descriptive data are presented under the mean, median, interquartile ranges, standard deviation, maximum and minimum value. To analyze the data, it was performed the multiple and linear simple regression (IC95%; p<0,05). Analyses was performed with the assistance of statistic software R (R CORE TEAM, 2019). Results: Forty-three elderly people was assessed, whose average age was 70.74 years (±6,66), ranging from 60 to 83 years. The average of handgrip strength (HS) was 22.44 kgf and the score of Short Physical Performance Battery (SPPB) was 8.47 (±2,09). The bivariate analysis of simple linear regression showed positive relation between HS and practice of physical activity (PPA); positive correlation between HS and mid upper arm circumference (MUAC) and significant inverse relation between the score of SPPB and age. The multiple model for HS showed significant relation with age, MUAC and years of study (R²=0,374; p<0,05). For SPPB, the model showed significant relation with age (R²=0,2524; p=0,001). Conclusion: This study showed that the muscle mass reserve, years of study and age were related to physical capacity among quilombolas elderly people. The higher the MUAC, the better the capacity of upper limbs, the higher the years of study, the worse the capacity of lower limbs. The older the person, the worse the capacity of upper and lower limbs. Thereby, it is suggested that these factors be priority in the development of strategies that aim maintenance and recovery of functionality.